Laboratory measurement of deformation-induced hydro-mechanical properties of reservoir rock in deep saline aquifers: An experimental study of Hawkesbury formation. (November 2016) - Perera, M.S.A.; Rathnaweera, T.D.; Ranjith, P.G.; Wanniarachchi, W.A.M.; Nasvi, M.C.A.; Abdulagatov, I.M.; Haque, A.
Abstract: The long-term integrity of CO2 storage in deep saline aquifers has become uncertain due to the unsteady character of surrounding factors, and the time-dependent nature of the aquifer's overburden load (the vertical stress imposed on the aquifer by the weight of overlying materials (rock/soil layers), which may vary over time as a result of natural incidents such landslides and earthquakes) is critical. The aim of this study is to identify the influence of overburden load variations on the long-term integrity of the CO2 storage process in deep saline aquifers. High-pressure tri-axial strength and permeability tests, along with acoustic emission (AE) and scanning electron microscopy (SEM) analyses, were conducted on Hawkesbury sandstone obtained from the Gosford basin. According to the results, the injection of CO2 into the Hawkesbury formation may dissolve aquifer rock minerals, enhancing aquifer flow performance and reducing aquifer strength. Increasing the stress applied on the aquifer causes aquifer flow ability to reduce to some extent due to pore matrix compaction. Further increase of the overburden pressure may accelerate the aquifer's flow performance due to dilation-induced pore opening. This permeability transition point occurs earlier at greater CO2 injection pressures and overlaps with the crack formation point of the aquifer rock mass. Therefore, weakening of the rock mass after the transition point can be expected. Importantly, this permeability transition point occurs at lower overburden loads after longer interaction of CO2 with the saline aquifer. This exhibits the long-term risk associated with CO2 sequestration in saline aquifers. Permeability enhancement after the transition point may also produce environmental disasters, such as sudden leakages of injected CO2 from the reservoir to surrounding fresh water aquifers (Evans et al. 2004; Little and Robert 2010), exceeding the specific rates proposed by many regulatory frameworks. Therefore, it is essential to study the long-term integrity of the sequestration process in order to develop a regulatory structure to meet the demands of deep saline sequestration projects. Highlights: The influence of overburden load on the long-term flow behaviour was observed. High-pressure permeability tests coupled with acoustic emission were performed. Increased overburden pressure accelerates the aquifer's dilation characteristics. Altered dilatancy characteristics affects the flow behaviour of reservoir rock.